2018
DOI: 10.3390/polym10030259
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chitosan Ascorbate Chirality on the Gelation Kinetics and Properties of Silicon-Chitosan-Containing Glycerohydrogels

Abstract: The influence of the chirality of chitosan ascorbate on the gelation kinetics and the properties of hybrid silicon-chitosan-containing glycerohydrogels were studied with a deep estimation of the stereospecificity of chitosan polysalts with l- and d-ascorbic acid diastereomers and their biological effects. It has been established that l- and d-diastereomerically enriched chitosan ascorbates are characterized by a positive Cotton effect and differ in the wavelength of the maximum of the dichroic band (250 and 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Similar changes in the kinetics of various chemical processes due to the differences in chirality have been described previously. [41][42][43] 1-Ethylquinidinium bromide was obtained with a yield of 82%. On the basis of the nuclear magnetic resonance spectra obtained, it was possible to conrm that the chemical structure of the product was correct.…”
Section: Synthesis and Identicationmentioning
confidence: 99%
“…Similar changes in the kinetics of various chemical processes due to the differences in chirality have been described previously. [41][42][43] 1-Ethylquinidinium bromide was obtained with a yield of 82%. On the basis of the nuclear magnetic resonance spectra obtained, it was possible to conrm that the chemical structure of the product was correct.…”
Section: Synthesis and Identicationmentioning
confidence: 99%
“…Показано, что в практическом плане для синтеза фармакологически актив-ных гидрогелей наиболее перспективны соли хитозана с фармакопейными органическими кислотами, в частности, аскорбиновой [20]. При исследовании стереоспецифичности полисолей хитозана с диастереомерами аскорбиновой кислоты установлено, что морфология конденсированной фазы L-аскорбата хитозана представлена анизодиаметрическими частицами с ярко выраженной оптической анизотропией, D-аскорбата хитозана -плотно упакованными конфокальными доменами сферической формы [28]. Обнаружено также, что гидрогелевые системы на основе D-аскорбата хитозана проявляют наибольшую антибактериальную активность и значимо ускоряют процессы адгезии и пролиферации клеточной культуры дермальных фибробластов.…”
Section: Doi: 1018500/1816-9775-2018-18-2-154-162unclassified
“…We have previously found that the interaction of an aqueous solution of chitosan ascorbate and an L-menthol solution in ethyl alcohol or its mixture with acetone is accompanied by crystalline phase separation of the mixture system to form anisodiametric fibrillar entities in the case of CS in L-AscA, which exhibit pronounced optical anisotropy in polarized light, or densely packed confocal domains of a shape close to spherical in the case of CS in D-AscA [5,6]. In this work, we will consider features of the crystallization of the L-menthol + ethanol system in an aqueous solution of CS in L-and D-AspA.…”
Section: Introductionmentioning
confidence: 99%